Corbynism : a critical approach - Bolton, Matt, active 2018; Pitts, Frederick Harry (Emerald Publishing Limited, 2018)
From the moment Jeremy Corbyn was elected Labour leader, Corbynism has been dismissed, derided or romanticised - but rarely taken seriously as a set of ideas on its own terms. From a left perspective, this book critically outlines the shared understanding of capitalism and its alternatives that unites the component parts of the Corbyn movement. Bypassing arguments over electability undermined by the 2017 election, 'Corbynism: A Critical Approach' decodes the central tenets of the Corbynist worldview, showing their coherence with contemporary political-economic shifts. Corbyns platform of protectionism at home and isolationism abroad, it contends, chimes with conspiratorial understandings of global capitalism as a rigged system common to populist nativism in an age of Trump and Brexit.
Includes index.
Keywords: Europe, Western -- History -- 20th century.; Political Science, World -- European.; Politics & government.; elektronické knihy; electronic books